Estudios y diseño geométrico y estructural de la vía Nudillo - Dumarí del cantón Chilla, provincia de El Oro (abscisa 5+000 - 10+000). - Bonilla Astudillo, María Teresa (2015)
In our country in recent years road development has been considerable since the roads are critical to the development of society by allowing people to communicate with each other, thereby ensuring economic and social development of the country importance. One aspect that is very important when making a draft pathway is planning, as this will allow us to obtain the information necessary for the successful completion of the project by providing important data that will ensure the efficient and economic operation thereof. This academic work aims to make the "Study and Geometric Design and structural Knuckle way - Dumari of Chilla Canton Province of El Oro (Abscisa 5 + 000-10 + 000)" to allow the construction of it and so the growing populations involved to solve the great road needs presented by these sectors.